Asymmetric Effect of Shadow Economy on Environmental Pollution in Egypt: Evidence from Bootstrap NARDL Technique - Gamal, Awadh Ahmed Mohammed; David, Joseph; Noor, Mohd Asri Mohd; Hussin, Mohd Yahya Mohd; Viswanathan, K. Kuperan (International Journal of Energy Economics and Policy, 2024)
This study examines the asymmetric effect of shadow economy on environmental pollution in Egypt during the 1970 and 2022 period. Using the bootstrap nonlinear autoregressive distributed lag (NARDL) bounds-testing approach, the study presents evidence of nonlinear cointegrating relationship between environmental degradation (carbon emission) and shadow economic activities (alongside globalisation, urbanisation, GDP per capita, and industrial growth). In addition, the results demonstrate that the impact of shadow economy (SE) on environmental pollution (ENV) is nonlinear, with the positive shock in shadow economy promoting environmental degradation and negative shocks promoting environmental quality, both in the short- and long-run. However, the study discovered that the magnitude of the impact of the SE on ENV is larger in the short-run. This is further validated by the dynamic ARDL simulation technique which demonstrates that the immediate effect of the SE on ENV is large. Additionally, the results suggest that income growth, urbanisation, and industrial growth are important drivers of environmental pollution. Therefore, the study recommends the adoption, and most importantly, implementation, of policies and strategies geared towards reducing the shadow economy, and consequently environmental pollution.